PERANCANGAN ALAT BANTU PETERNAKAN AYAM PETELUR MENGGUNAKAN METODE ERGONOMIC FUNCTION DEPLOYMENT (EFD) (Studi Kasus Peternakan Barokah Di Desa Kali Beji, Kebumen) - Stefanus Hergiyan (2022)
Observations on barokah laying hens in Kali Beji Village, Kebumen, it is known that work is still done manually, such as taking eggs and also feeding. Workers have to take 900 eggs at peak production for 1 house sometimes manually and feed 1080 chickens manually, in the Rapid Entire Body Assessment (REBA) analysis, 8-10 points are obtained, 1 point is worth 7 and also complaints from high-level workers and medium based on Nordic Body Map (NBM). analysis of satisfaction and importance found that the first priority of the tool does not need to be looking down and reaching far which can cause complaints. The tool is designed based on anthropometry with 50th percentile on the handle of the feed tool, Tabel height, foam width, foam length, egg take handle, distance between feeder poles sequentially 4,81cm,92,25cm, 37,25cm, 38cm, 4,81cm , 80.12cm and for the distance between the handles using the 95th percentile of 46.91cm to help the work of taking eggs and feeding. the Rapid Entire Body Assessment (REBA) value of the new tool is reduced to 4 for activities to pick up eggs up and down also push tools, then score 3 to tidy up eggs due to an improvement in position while working, then the movement made by workers was also reduced, to take eggs they did 120-240 movements per day and immediately arranged them, while for feeding it was done by pushing tool.